2011
DOI: 10.1016/j.jhep.2010.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive evaluation of hepatic fibrosis using acoustic radiation force-based shear stiffness in patients with nonalcoholic fatty liver disease

Abstract: Background & Aims Nonalcoholic fatty liver disease (NAFLD), the most common form of chronic liver disease in developed countries, may progress to nonalcoholic steatohepatitis (NASH) in a minority of people. Those with NASH are at increased risk for cirrhosis and hepatocellular carcinoma. The potential risk and economic burden of utilizing liver biopsy to stage NAFLD in an overwhelmingly large at-risk population are enormous; thus, the discovery of sensitive, inexpensive, and reliable noninvasive diagnostic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
244
2
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 321 publications
(265 citation statements)
references
References 29 publications
15
244
2
4
Order By: Relevance
“…An example of the relationship between radiation force-derived shear modulus estimates and biopsy proven hepatic fibrosis stage is shown in figure 4 [57].…”
Section: Shear Wave Speed Reconstruction Methodsmentioning
confidence: 99%
“…An example of the relationship between radiation force-derived shear modulus estimates and biopsy proven hepatic fibrosis stage is shown in figure 4 [57].…”
Section: Shear Wave Speed Reconstruction Methodsmentioning
confidence: 99%
“…In that study, BMI > 40 kg/m 2 was not a limiting factor for ARFI imaging, and no correlation was noted between BMI and shear stiffness. As a result, the authors concluded that ARFI is a promising imaging modality for detecting advanced fibrosis in patients with obesity-related liver disease [50] . TE and ARFI using the standard or the XL probes were also compared for the diagnosis of liver fibrosis in 61 patients with NAFLD/NASH [53] .…”
Section: Acoustic Radiation Force Impulsementioning
confidence: 98%
“…With this method, the elasticity of the liver is calculated from short-duration acoustic pulses of a fixed frequency targeted to one region. As with TE, the result is expressed in kPa [35,50] . ARFI has been suggested for patients with a high BMI [51] , which can affect the accuracy of liver stiffness measurements.…”
Section: Acoustic Radiation Force Impulsementioning
confidence: 99%
See 2 more Smart Citations